Penerapan Metode Talaqqi dalam Program Tahfidzul Qur’an di Pondok Pesantren Riyadlus Sholihin Kota Probolinggo - Sholeh, Ahmad Suyuti; Nuha, Nazahah Ulin (Lembaga Yasin AlSys, 2025)
This study aims to examine the implementation of the Talaqqi method in the Tahfidzul Qur'an program at Riyadlus Sholihin Islamic Boarding School, as well as to evaluate its impact on memorization proficiency. The education of Tahfidzul Qur’an within Islamic boarding schools encounters numerous challenges, particularly regarding the adoption of effective teaching methodologies and the integration of technology to enhance students' memorization capabilities. Utilizing a qualitative approach with a case study design, this research focuses on the application of the Talaqqi method at Riyadlus Sholihin Islamic Boarding School. This methodological framework allows for a comprehensive exploration of the learning processes and the dynamics of interaction between educators and students. The findings of this study support the theory of active learning in the context of Qur'anic education, positioning the Talaqqi program as a highly effective strategy for Qur'anic memorization. This method transcends being a mere instructional technique; it embodies a pedagogical process that emphasizes the importance of quality interactions between educators and students, which are often vital for achieving successful outcomes in memorization. Moreover, this research not only reinforces the theory of active learning but also highlights practical applications pertinent to Qur'anic education, addressing the contemporary challenges and needs faced by students. It provides valuable insights for educators on effective strategies, advocating for the use of technology as a complementary tool while underscoring the critical role of personal interaction intrinsic to the Talaqqi method.